Investigation on the Use of Artificial Intelligence in Reading Comprehension Class in Indonesian Setting - Pratiwi, Aisyah; Lestari, Ria (English Education Department, 2025)
This research aims to explore the use of AI in reading comprehension classes in Indonesia. This explorative research uses various references to gain a conclusion on the investigation of AI used in teaching reading comprehension. The use of artificial intelligence in reading comprehension classes in Indonesia offers significant benefits, including personalized learning, material accessibility, fast feedback, and increased student engagement. However, challenges such as lack of infrastructure, teacher training, and concerns about data privacy need to be addressed to maximize the potential of AI in education. Various successful implementation examples show that with the right support, AI can be an effective tool in improving students’ reading comprehension in Indonesia. Therefore, it is important for all stakeholders to collaborate in creating a learning environment that supports the use of this technology.